Heterogeneity in general practitioners' preferences for quality improvement programs: A choice experiment and policy simulation in France - Mehdi Ammi; Christine Peyron (Health Economics Review, 2016)
Despite increasing popularity, quality improvement programs (QIP) have had modest and variable impacts on enhancing the quality of physician practice. We investigate the heterogeneity of physicians' preferences as a potential explanation of these mixed results in France, where the national voluntary QIP - the CAPI - has been cancelled due to its unpopularity. We rely on a discrete choice experiment to elicit heterogeneity in physicians' preferences for the financial and non-financial components of QIP. Using mixed and latent class logit models, results show that the two models should be used in concert to shed light on different aspects of the heterogeneity in preferences. In particular, the mixed logit demonstrates that heterogeneity in preferences is concentrated on the pay-for-performance component of the QIP, while the latent class model shows that physicians can be grouped in four homogeneous groups with specific preference patterns. Using policy simulation, we compare the French CAPI with other possible QIPs, and show that the majority of the physician subgroups modelled dislike the CAPI, while favouring a QIP using only non-financial interventions. We underline the importance of modelling preference heterogeneity in designing and implementing QIPs.
Keywords: I11; I18; C25; 330; General practitioners; Discrete choice experiment; Mixed logit; Latent class logit; Quality improvement programs; Policy simulation